Association between vitamin D and urinary tract infection in children - Abolfazl Mahyar; Parviz Ayazi; Sara Safari; Reza Dalirani; Amir Javadi; Shiva Esmaeily (Korean Pediatric Society, 2018)
PurposeThe present study aimed to determine the relationship between serum 25-hydroxyvitamin D (25(OH)D) level and Urinary tract infections (UTIs) in children.MethodsIn this case-control study, 70 children with UTI (case group) were compared with 70 healthy children (control group) in terms of serum 25(OH)D levels. The children were between 1 month and 12 years of age. Serum 25(OH)D levels were measured using enzyme-linked immunosorbent assay (ELISA). The results were analyzed and compared between both groups.ResultsAmong 70 children with UTI (case group), 5 children (7.2%) were male and 65 (92.8%) were female. Among the healthy children (control group), 9 (12.8%) and 61 children (87.2%) were male and female, respectively (P=0.39). The mean±standard deviation of age in the case and control groups were 53.2±35.6 and 36.1±60.2 months, respectively (P=0.24). The mean level of serum 25(OH)D in the case group was significantly higher than that of the control group (20.4±8.6 ng/mL vs. 16.9±7.4 ng/mL, P=0.01).ConclusionThis study showed that there was a relationship between serum 25(OH)D levels and UTI in children. It seems that 25(OH)D plays a role in the pathogenesis of UTI.